Transformation of Islamic Law in the Indonesian National Legal System: Analysis of Its Evolution and Implementation - Wahid, Sahid; HL, Rahmatiah; Akmal, Andi (Journal of Public Representative and Society Provision, 2025)
Islamic law has an important position as a legal system that is not only derived from divine revelation, but also reflects the moral and spiritual values ​​of Muslims. This study aims to describe the characteristics of Islamic law by examining in depth the conceptual differences between Islamic law, sharia, and fiqh, and tracing its main sources, namely the Qur'an and hadith. In addition, this paper also discusses the characteristics of Islamic law which are flexible, justice-oriented, and able to adapt to the social dynamics of society. The implementation of Islamic law in Indonesia is an additional focus in this article, considering the diversity of legal systems in Indonesia that allow Islamic law to coexist with national law, especially in aspects of family law and sharia economics. Through a descriptive-analytical approach, this article concludes that Islamic law has great potential to become an inclusive and contextual legal solution, as long as it is understood proportionally in accordance with its normative and historical foundations. Thus, a comprehensive understanding of the characteristics of Islamic law is needed to strengthen its role in the national legal system and the lives of contemporary Muslim society.